2023
DOI: 10.34172/hpp.2023.03
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy: A Systematic review of cognitive determinants

Abstract: Background: Although mass vaccination is considered one of the most effective public health strategies during the pandemic, in the COVID-19 era, many people considered vaccines unnecessary and, or doubted the effectiveness of the COVID-19 vaccine. This review aimed to tabulate cognitive causes of COVID-19 vaccination hesitancy, which may help public health policymakers overcome the barriers to mass vaccinations in future pandemics. Methods: For this systematic review, studies pertaining to COVID-19 vaccine hes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 117 publications
1
8
0
Order By: Relevance
“…In light of these findings, it becomes evident that targeted strategies to increase awareness and discernment regarding online vaccine information are indispensable. The study [12] corroborates our observation on the significant influence of exposure to fake news on vaccine hesitancy and the importance of multifaceted strategies to mitigate this effect. This includes not only improving digital literacy among the targeted audience but also implementing communication campaigns that specifically address their concerns, clarify doubts, and proactively debunk myths.…”
Section: Discussionsupporting
confidence: 89%
“…In light of these findings, it becomes evident that targeted strategies to increase awareness and discernment regarding online vaccine information are indispensable. The study [12] corroborates our observation on the significant influence of exposure to fake news on vaccine hesitancy and the importance of multifaceted strategies to mitigate this effect. This includes not only improving digital literacy among the targeted audience but also implementing communication campaigns that specifically address their concerns, clarify doubts, and proactively debunk myths.…”
Section: Discussionsupporting
confidence: 89%
“…Our results also revealed that the decline in the protection conferred by COVID-19 vaccines against new variants and over time had a negative influence on participants’ confidence in these vaccines, potentially leading to a decrease in willingness to receive a booster dose. Perceived efficacy of the vaccine remains one of the most significant reasons for people to get vaccinated, either for primary COVID-19 vaccine series or booster dose(s) [ 19 , 23 , 24 ]. Participants’ perceived risk of COVID-19 also decreased during the pandemic, particularly if they had already received vaccine doses or contracted the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that prior COVID-19 infection could negatively influence COVID-19 vaccine willingness [ 19 , 25 ]. Low-risk perception of the threat of COVID-19 and low perceived efficacy of the vaccines are known determinants of COVID-19 vaccine hesitancy [ 24 ], including for the receipt of booster doses [ 19 , 23 , 26 ]. These factors are also associated with low COVID-19 vaccine acceptance among parents in this study, as well as in others [ 11 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… 8 Furthermore, differently from screening procedures that involve mostly undergoing minimally invasive tests, vaccinations include the injection of a substance into the body of healthy people, an action that may require strong vaccine confidence. 9 In addition, there are other motivations underlying adherence to these two interventions that are likely to be different: while for screening the benefits to undergo a diagnostic test are clearly individual, vaccinations may be perceived to contribute more to increase population health than to protect individuals. 10 Another important difference to take into account regards the target population.…”
Section: Dear Editormentioning
confidence: 99%